2000
DOI: 10.1063/1.481972
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the ultrafast photodissociation of electronically excited CF2I2 molecules by femtosecond time-resolved photoelectron spectroscopy

Abstract: Articles you may be interested inFollowing the excited state relaxation dynamics of indole and 5-hydroxyindole using time-resolved photoelectron spectroscopy Electron configuration changes in excited pyrazine molecules analyzed by femtosecond time-resolved photoelectron spectroscopy Time-resolved photoelectron spectroscopy of the allyl radical: The lifetimes of the ultraviolet bands

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…The formation scheme of in which the minimum number of photons are absorbed is the (2 + 1‘) photon process, where the prime indicates the absorption of 264 nm pump photons; see Figure . Previous time-resolved ion imaging studies have shown that in the case of CF 3 I and CF 2 I 2 the photon schemes using the minimum number of photons are the dominant channels. , This was confirmed by coincidence imaging measurements 21 and time-resolved electron measurements . In the experiment we reduced the fluences of both the pump and probe laser to only produce the fragments of interest and to prevent photon processes involving more photons.…”
Section: Resultssupporting
confidence: 52%
“…The formation scheme of in which the minimum number of photons are absorbed is the (2 + 1‘) photon process, where the prime indicates the absorption of 264 nm pump photons; see Figure . Previous time-resolved ion imaging studies have shown that in the case of CF 3 I and CF 2 I 2 the photon schemes using the minimum number of photons are the dominant channels. , This was confirmed by coincidence imaging measurements 21 and time-resolved electron measurements . In the experiment we reduced the fluences of both the pump and probe laser to only produce the fragments of interest and to prevent photon processes involving more photons.…”
Section: Resultssupporting
confidence: 52%
“…23 Another possibility is that the initially excited state decays very rapidly into the lower-lying excited state similarly to what was proposed for the excited CF 2 I 2 molecule (30 fs decay). 24,25 An interpretation assigning the short-time dynamics at all probe wavelengths to the CH 2 Br radical is not consistent with the amount of excess vibrational energy stored in the radical immediately after the photodissociation. Since only about 14% of the total available energy in C-I breaking appears as vibrational excitation of the CH 2 Br radical 12 we expect that the hot CH 2 Br only contributes to the observed early-time dynamics at probe wavelengths shorter than ∼370 nm.…”
Section: Resultsmentioning
confidence: 97%
“…30 The formation of molecular iodine is observed only upon excitation of CF 2 I 2 at 193 nm ͑6.5 eV͒. [33][34][35][36] In contrast to the gas-phase photochemistry, excitation of CF 2 I 2 in n-hexane with a single 350 nm photon ͑3.54 eV͒ leads to the ultrafast formation of molecular iodine in a 32% quantum yield. 37 Despite the fact that resonance Raman spectra of CF 2 I 2 are strongly solvent dependent, 38,39 the several picosecond build up of I 2 was observed in a wide range of solvents ͑methanol, acetonitrile, linear alkanes, and chlorinated alkanes͒.…”
Section: Introductionmentioning
confidence: 99%